2022
DOI: 10.3390/toxics10030104
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the Pesticides Imidacloprid, Difenoconazole and Glyphosate Alone and in Binary and Ternary Mixtures to Winter Honey Bees: Effects on Survival and Antioxidative Defenses

Abstract: To explain losses of bees that could occur after the winter season, we studied the effects of the insecticide imidacloprid, the herbicide glyphosate and the fungicide difenoconazole, alone and in binary and ternary mixtures, on winter honey bees orally exposed to food containing these pesticides at concentrations of 0, 0.01, 0.1, 1 and 10 µg/L. Attention was focused on bee survival, food consumption and oxidative stress. The effects on oxidative stress were assessed by determining the activity of enzymes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 132 publications
2
13
0
Order By: Relevance
“…In contrast, the tebuconazole pulse did not reduce the survival of O. bicornis females chronically exposed to imidacloprid in our study. These results are in line with other studies in which honey bees chronically exposed to imidacloprid-tetraconazole (Zhu et al 2017b) and imidacloprid-difenoconazole (Pal et al 2022) mixtures did not yield synergistic effects; similarly, no interactions between imidacloprid (15 µg L −1 ) and myclobutanil were found following chronic oral exposure in O. bicornis (Azpiazu et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the tebuconazole pulse did not reduce the survival of O. bicornis females chronically exposed to imidacloprid in our study. These results are in line with other studies in which honey bees chronically exposed to imidacloprid-tetraconazole (Zhu et al 2017b) and imidacloprid-difenoconazole (Pal et al 2022) mixtures did not yield synergistic effects; similarly, no interactions between imidacloprid (15 µg L −1 ) and myclobutanil were found following chronic oral exposure in O. bicornis (Azpiazu et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in the head, CAT expression was significantly reduced by imidacloprid but was significantly increased by exposure to fenitrothion, carbaryl, amitraz, and bifenthrin ( Fig 5 ). Similar large variations in antioxidant enzyme activities, including SOD , CAT , and GST , were investigated in different tissues (head, midgut, and abdomen) of honey bees exposed to imidacloprid, glyphosate, and difenoconazole, alone and in binary and ternary mixtures [ 81 ]. This suggests that antioxidant enzymes might respond differently in different body parts and to different types of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SOD1 in the head and the fat body was significantly induced by seven pesticides, suggesting that SOD1 could be a candidate molecular marker. However, SOD1 is a typical antioxidant enzyme, and oxidative stress is generated by various stressors, such as chemicals [79][80][81], heavy metals [50], flight, and age [93] in honey bees; therefore, caution is needed when using SOD1 as a molecular marker to investigate the damage caused by pesticides.…”
Section: Plos Onementioning
confidence: 99%
“…A recent study shows that chronic oral exposure of A. mellifera to GLY (0.0001 and 0.01 mg/L) can alter the functioning of some enzymes in the head (GTS, GR, GPbox and SOD enzymes) and in the midgut (SOD enzymes; G6PDH, GST and CAT) (Pal et al, 2022). Another study also showed biochemical changes in A. mellifera after chronic oral contact with GLY, comparing bees with and without the intestinal microbiota, showing that the absence of these microorganisms can cause changes in the head (LDH enzyme) and midgut (GST enzyme) (Almasri et al, 2022).…”
Section: Sublethal Effects Of Glyphosate On Beesmentioning
confidence: 99%